A novel quantification method for retinal pigment epithelium phagocytosis using a very-long-chain polyunsaturated fatty acids-based strategy - Gao, Fangyuan; Tom, Emily; Lieffrig, Stephanie A.; Finnemann, Silvia C.; Skowronska-Krawczyk, Dorota (Frontiers in Molecular Neuroscience, 2023)
The vertebrate retinal pigment epithelium (RPE) lies adjacent to the photoreceptors and is responsible for the engulfment and degradation of shed photoreceptor outer segment fragments (POS) through receptor-mediated phagocytosis. Phagocytosis of POS is critical for maintaining photoreceptor function and is a key indicator of RPE functionality. Popular established methods to assess RPE phagocytosis rely mainly on quantifying POS proteins, especially their most abundant protein rhodopsin, or on fluorescent dye conjugation of bulk, unspecified POS components. While these approaches are practical and quantitative, they fail to assess the fate of POS lipids, which make up about 50% of POS by dry weight and whose processing is essential for life-long functionality of RPE and retina. Here, we have developed a novel very-long-chain polyunsaturated fatty acids (VLC-PUFA)-based approach for evaluating RPE phagocytic activity by primary bovine and rat RPE and the human ARPE-19 cell line and validated its results using traditional methods. This new approach can be used to detect in vitro the dynamic process of phagocytosis at varying POS concentrations and incubation times and offers a robust, unbiased, and reproducible assay that will have utility in studies of POS lipid processing.